EXCLI Journal; 21:Doc487; ISSN 1611-2156 2022
DOI: 10.17179/excli2021-4572
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the adverse outcome of subtypes of heart failure with preserved ejection fraction defined by machine learning: a systematic review focused on defining high risk phenogroups

Abstract: The ability to distinguish clinically meaningful subtypes of heart failure with preserved ejection fraction (HFpEF) has recently been examined by machine learning techniques but studies appear to have produced discordant results. The objective of this study is to synthesize the types of HFpEF by examining their features and relating them to phenotypes with adverse prognosis. A systematic search was conducted using the search terms “Diastolic Heart Failure” OR “heart failure with preserved ejection fraction” OR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 136 publications
(265 reference statements)
0
2
0
Order By: Relevance
“…The results of our cluster analyses identified seven phenotypes for each group of study (AF, CAD, OSA) and showed that HBP was the most prevalent comorbidity associated to CAD, OSA, and AF. Cluster analytic techniques used in several studies have proposed phenotypic groups for CVD risk and include HBP, AF, CAD and renal disfunction as comorbidities with the highest risk for heart failure and death ( 46 ). The role of OSA in the phenotypes groups of CVD risk has not been extensively studied.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our cluster analyses identified seven phenotypes for each group of study (AF, CAD, OSA) and showed that HBP was the most prevalent comorbidity associated to CAD, OSA, and AF. Cluster analytic techniques used in several studies have proposed phenotypic groups for CVD risk and include HBP, AF, CAD and renal disfunction as comorbidities with the highest risk for heart failure and death ( 46 ). The role of OSA in the phenotypes groups of CVD risk has not been extensively studied.…”
Section: Discussionmentioning
confidence: 99%
“…Effective space manipulation leads to improved model performance by ensuring representations of both text and image modalities are compatible and can be efficiently combined to make diagnostic predictions. In contrast, MED-UniC models involve medical data streams from multiple sources of data, such as imaging (e.g., radiography) and text data (e.g., consult notes) [31] . Medical vision and language pre-training (MED-VLP) hopes to integrate and jointly process these data to generalize representations from large-scale medical image-text data.…”
Section: Brs and Multi-modal Training In Medical Ai Modelsmentioning
confidence: 99%